Grammatical Cohesion in Oral Narration: An Analysis of Podcast UR Cristiano Playlist - Cahya Maulana, Yudha; Agry Pramita; Cipto Wardoyo (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study examines the use of grammatical cohesion elements in oral narratives on podcasts, focusing on their contribution to the cohesiveness of oral discourse. This study focuses on its contribution to the cohesion of spoken discourse. It aims to identify and analyze the distribution of cohesion elements-reference, conjunction, substitution, and ellipsis-in the UR Cristiano. The analysis of the data shows that reference is the most frequently used cohesion element, accounting for 59% of the total occurrences, indicating its dominant role in connecting parts of the narrative and clarifying the flow of the conversation. Conjunctions followed with a significant percentage of 21%, assisting in the logical progression of ideas. Substitution and ellipsis appear with lower frequency, at 5% and 15% respectively, but still contribute by reducing repetition and enriching text variety. The findings highlight the multiple functions of grammatical cohesion elements in constructing cohesive oral narratives. This research provides insight into the structural strategies used in podcast discourse and confirms the importance of cohesion in easing listeners' understanding. Keywords: grammatical cohesion, oral narration, podcasts